Measurement of Vertical Profiles of the Atmospheric Surface Layer With Low-Cost Instrumentation on Board a Drone (Global Journal of Human-Social Science, 2023)
Atmospheric natural disasters can have their damage mitigated if meteorological alerts are disseminated on time Among the ways to get data related to weather conditions are the use of atmospheric profilers and numerical models Such resources can be used for studies related to the surface layer which covers a range from 20 to 200 meters below the low troposphere In order to make atmospheric experiments achievable without great financial expenditure a low-cost atmospheric profiler was developed together with the Laboratory of Monitoring and Numerical Modeling of Climate Systems LAMMOC of the Federal Fluminense University UFF to be on board a drone and based on prototyping with Arduino which had as sensors the DHT22 for measuring temperature and relative humidity and the BMP280 for measuring atmospheric pressure Thus this profiler was used in an experiment from which atmospheric vertical profiles were generated and compared with profiles generated by the numerical model Weather Research and Forecasting WRF and post-processed by the WRF-Python routines package As a result it was noticed that the observed data profiles described a behavior of the surface layer that indicates the occurrence of thermal inversion and change of regime of this layer from the stable passing through the neutral to the unstable With this it is evaluated that the method of using this profiler can be applied in several atmospheric studies such as atmospheric pollution and nowcasting weather forecast as well as its potential for use in areas such as operational meteorology and assimilation of data from numerical models shows to be promising
Keywords: natural disasters; surface layer; low-cost arduino instrumentation